Hazelnut Shells as a Tenable Biosorbent for Basic Red 18 Azo Dye Removal - Naji Agilee; Tijana Spasojević; Milica Delić; Đorđe Ogrizović; Isabel R. Gria; Nevena Prlainović; Maja Đolić (Separations)
The increasing pollution from the textile industry, particularly organic azo dyes, presents a significant environmental challenge, necessitating the development of effective and sustainable treatment methods. This study investigates the adsorption potential of hazelnut shells (raw—RHSs; modified—MHSs) for the removal of organic azo dyes from aqueous solutions. As biomass, hazelnut shells are biodegradable and represent a sustainable alternative to synthetic adsorbents, thereby reducing the ecological footprint. Through a series of batch adsorption experiments, the influence of various parameters, including pH, contact time, concentration, and temperature, on adsorption capacity was examined. Characterization of the hazelnut shells was conducted using optical microscopy and ATR-FTIR, XRF, and XRD spectroscopy, confirming its suitability as a biosorbent. The analyzed isotherms showed that adsorption onto RHSs was best fitted by the Freundlich model, while adsorption onto MHSs was best fitted by the Temkin model. Kinetic studies demonstrated that the adsorption process is well described by the pseudo-second-order model, suggesting that chemical adsorption plays a significant role. The maximal adsorption capacity was 62.11 mg/g for RHSs and 80.65 mg/g for MHSs, highlighting the potential of hazelnut shells as an abundant, low-cost, and eco-friendly adsorbent. Furthermore, recycling studies indicated the feasibility of the adsorbent, underscoring its practical applicability in real scenarios.